(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Research is aimed at defining the risks that the sales activity of the General Company for Leather Industries about a special, then diagnose these risks, through a set of indicators, which indicate its existence and try to overcome them, and minimizing the negative effects on those activities. The research found some conclusions, which emphasizes that the General Company for Leather Industries, suffer from a lack of profit, and a large decrease in sales; a result of absence of demand on its products and rising cost of the expenses to income ratio of, which was reflected in the cost per unit produced. Also the conclusions shown that the number of sales outlets for the company to cover the geographical area is not enough, in spite of the availability of a greater opportunity, to increase sales which is reflected negatively on the magnitude of sales. The weakness of government support for the company directly and indirectly, has weakened its ability competition its products toward similar products in the domestic market. Finally research Some of the recommendations included, which we hope will be of great importance to strengthen the march of this company, which is one of the most important sectors of the industry, the research includes some of the most important recommendations were: Supporting local industry and protect, availability of all that is needed to fill the requirements of primary and raw materials, and imposing of customs tariff on imported products, increase sales magnitude, achieve profitability, and improving competitiveness, and pre-planning diagnose potential risks, and reduce the raised and to develop a strategy to transfer risk through insurance for example.